Comparative effectiveness of various physical exercise interventions on executive functions and related symptoms in children and adolescents with attention deficit hyperactivity disorder: A systematic review and network meta-analysis - Zhu, Feilong; Zhu, Xiaotong; Bi, Xiaoyu; Kuang, Dongqing; Liu, Boya; Zhou, Jingyi; Yang, Yiming; Ren, Yuanchun (Frontiers in Public Health, 2023)
Background Physical exercise has been recommended as an important nonpharmacological therapeutic strategy for managing attention deficit hyperactivity disorder (ADHD). We conducted a network meta-analysis (NMA) to assess the comparative impact of different physical exercise modalities on enhancing executive functions (EFs) and alleviating symptoms in children and adolescents with ADHD. Methods We searched Web of Science, PubMed, Embase, Cochrane Central Register of Controlled Trials, SPORTDiscus, PsycINFO, CNKI, and clinical trials databases from inception to October 20, 2022. Randomized controlled trials (RCTs) and quasi-experimental studies investigating physical exercise for ADHD-related symptoms of hyperactivity/impulsivity and inattention, and executive functions were included. The frequentist random-effect NMA method was applied to pool the results. Results A total of 59 studies (including 39 RCTs, 5 quasi-RCTs, and 15 self-controlled trials) published between 1983 and 2022 were incorporated into the systematic review, of which 44 studies with 1757 participants were eligible for meta-analysis. All types of physical exercise were effective in improving EFs (SMD = 1.15, 95% CI: 0.83 to 1.46), and open-skill activities which require participants to react in a dynamically changing and externally paced environment induced the most incredible benefits for executive functions (SUCRA = 98.0%, SMD = 1.96, and 95% CI: 1.15 to 2.77). Subgroup analyses for EFs revealed varied findings that open-skill activities were the most promising physical exercise type for improving inhibitory control (SUCRA = 99.1%, SMD = 1.94, and 95% CI: 1.24 to 2.64), and closed-skill activities dominated by aerobic exercises had a slightly higher probability of being the most promising physical exercise intervention for working memory (SUCRA = 75.9%, SMD = 1.21, and 95% CI: −0.22 to 2.65), and multicomponent physical exercise tended to be the most effective in cognitive flexibility (SUCRA = 70.3%, SMD = 1.44, and 95% CI: −0.19 to 3.07). Regarding ADHD-related symptoms, closed-skill activities dominated by aerobic exercises might be more advantageous for hyperactivity/impulsivity (SUCRA = 72.5%, SMD = -1.60, and 95% CI: −3.02 to −0.19) and inattention (SUCRA = 96.3%, SMD = -1.51, and 95% CI: −2.33 to −0.69) improvement. Conclusion Physical exercise can significantly help to alleviate the symptoms of ADHD and improve executive functions in children and adolescents with ADHD. Most of all, to promote adherence to treatment, they should be encouraged to perform the physical exercises that they enjoy most.